Late Recurrence in Ovarian Dysgerminoma Presenting as a Primary Retroperitoneal Tumor: A Case Report and Review of the Literature - Yuichiro Sato; Tohru Hayashi; Hidetaka Yamamoto; Ichiro Niina; Naoya Kuroki; Takeshi Iwamura; Junji Onishi (Case Reports in Pathology)
Ovarian dysgerminoma is a rare type of germ cell tumor. The majority of patient relapses occur within 2 years of diagnosis. Here, we report the case of a 74-year-old woman with a history of ovarian dysgerminoma 39 years earlier. The patient visited the hospital presenting with heartburn. An abdominal computed tomography (CT) revealed a right retroperitoneal mass, and a primary retroperitoneal tumor was suspected. She underwent surgical resection of the retroperitoneal tumor. Histological examination confirmed a metastatic dysgerminoma to the retroperitoneum. Postoperative CT showed paraaortic and cervical lymph node metastases. The patient was treated with bleomycin, etoposide, and cisplatin chemotherapy. This case demonstrates the difficulties that may be encountered in the differential diagnosis of a retroperitoneal mass and underlines the necessity for understanding a patient’s clinical history.